The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.1101/2021.10.08.463726
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of Iron-Sulfur (Fe-S) and Zn-binding Sites Within Proteomes Predicted by DeepMind’s AlphaFold2 Program Dramatically Expands the Metalloproteome

Abstract: DeepMind′s AlphaFold2 software has ushered in a revolution in high quality, 3D protein structure prediction. In very recent work by the DeepMind team, structure predictions have been made for entire proteomes of twenty-one organisms, with >360,000 structures made available for download. Here we show that thousands of novel binding sites for iron-sulfur (Fe-S) clusters and zinc ions can be identified within these predicted structures by exhaustive enumeration of all potential ligand-binding orientations. We … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
0
0
0
Order By: Relevance
“…Because TPEN has a higher affinity for zinc cations than iron, it can exclude captured zinc more efficiently than iron and other metal cations. An article regarding the mathematical prediction of the ion-binding site of metalloproteins revealed that AlphaFold2 is a useful and extensive tool for protein annotation of zinc ion binding (38). This report endorses our analysis strategy for annotating the 4 conserved cysteines of ORF34 as binding sites for metal cations.…”
Section: Discussionsupporting
confidence: 56%
“…Because TPEN has a higher affinity for zinc cations than iron, it can exclude captured zinc more efficiently than iron and other metal cations. An article regarding the mathematical prediction of the ion-binding site of metalloproteins revealed that AlphaFold2 is a useful and extensive tool for protein annotation of zinc ion binding (38). This report endorses our analysis strategy for annotating the 4 conserved cysteines of ORF34 as binding sites for metal cations.…”
Section: Discussionsupporting
confidence: 56%